Comparative Analysis of Mahr Practices in Indonesia and Saudi Arabia: Sociocultural and Economic Perspectives - A'zdom, Muhammad Khofidul; Asilah, Amirah Salwa (Journal of Studies on Art, Culture and Society, 2025)
Mahr the obligatory bridal gift in Islamic marriage functions simultaneously as a religious requirement, a cultural symbol, and an economic transfer. This comparative study examines contemporary mahr practices in Indonesia and Saudi Arabia, identifying the sociocultural, religious, and economic factors that shape mahr values and meanings in each country. Employing a mixed‑methods design, the study combines survey data from 612 married couples (Indonesia = 324; Saudi Arabia = 288) with 48 semi‑structured interviews. Quantitative results reveal significant cross‑national differences in median mahr amounts (USD 1,050 in Indonesia vs. USD 13,800 in Saudi Arabia) and in the weight of predictors such as bride’s education and family income. Qualitative analysis uncovers convergent themes of religious duty and social prestige, but divergent narratives around economic burden and women’s agency. By integrating both data strands, the study contributes a nuanced understanding of how local cultures negotiate global Islamic norms. Policy implications include the need for premarital counseling focused on financial literacy and the potential role of Islamic legal institutions in promoting equitable mahr agreements.